Artaka fish farm community empowerment in karang kepanjen village, trimulyo, sleman, sleman regency - Iswanto Suwarno; Adhianty Nurjanah; Barbara Gunawan; Nia Maharani Raharja; Alfian Ma’arif; Dhiya Uddin Rijalusalam; Rachmad Andri Atmoko; Sashikala Mishra (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2021)
Kampung Karang is geographically located at an altitude of 280 meters above sea level. Designated as a green belt area or supporting food needs, the hamlet area has the potential for excellence in the agricultural sector. Kampung Karang has an SME of catfish farming farmers, namely Artaka Fish Farm. Artaka Fish Farm "Fish Farming SMEs" is located in an agricultural area in Sleman Regency, precisely in Karang Kepanjen Hamlet, Trimulyo Village, Sleman District, Sleman Regency, Special Region of Yogyakarta has been carrying out fish farming activities since 2012. Actually these SMEs have quite a market opportunity. great for aquaculture. However, this opportunity brings consequences and problems, namely the lack of a touch of innovation from the fish feeding system. The service team tries to offer solutions to these problems with a touch of science and technology, namely through the main activity of designing fish feeders. This fish feeder is controlled using an Arduino Uno type microcontroller. The DS1307 type real time clock module is used for scheduling fish feeders. This system can be arranged for scheduling fish feeders. Fish feed is given to fish by means of a fish feeder according to a specified schedule.